Effects of pericapsular nerve group block on early postoperative cognitive function in older people undergoing hip arthroplasty: a randomized controlled clinical trial - Manhua Zhu; Qilu Ying; Lingzhi Wang; Ruifen Zhou; Yuliu Mei (BMC Geriatrics)
Abstract Background Pericapsular nerve group (PENG) block has emerged as a reliable analgesia technique for hip arthroplasty (HA). However, the effects of PENG block on perioperative neurocognitive disorder (PND) after HA has not yet been assessed. The present study aimed to investigate the effects of PENG block on early postoperative cognitive function in older people undergoing hip arthroplasty. Methods Sixty older patients undergoing HA under spinal anesthesia were randomly assigned to group P (n = 30) receiving PENG block with ropivacaine and patient-controlled intravenous analgesia (PCIA) pump with sufentanil after surgery or group C (n = 30) only receiving PCIA pump with sufentanil after surgery. The primary outcome was the Mini-Mental State Examination (MMSE) score at 7 days postoperatively. Secondary outcomes consisted of the incidence of PND 7 days postoperatively, the static VAS pain scores at 6, 12, 24, and 48 h postoperatively; cumulative sufentanil consumption and the requirement of rescue analgesia during the 0–24 h period after surgery; quality of recovery-15 (QoR-15) scale scores at 24 h postoperatively; and the plasma levels of high mobility group box protein 1 (HMGB1) preoperatively and 1 day after surgery, and adverse events. Results After surgery, the PENG block group had higher MMSE score than the control group at 7 days postoperatively (27.0 ± 1.8 vs. 26.1 ± 1.7, P = 0.048), with a mean difference of 0.9 (95%CI, 0.1–0.9). The incidence of PND at 7 days postoperatively was 6.7% in group P, lower than that of 30% in group C (P = 0.044). In group P, the static VAS scores at 6, 12, and 24 h postoperatively were significantly lower than those in group C (all P < 0.05). Compared with group C, the cumulative sufentanil consumption and the number of patients required rescue analgesia during the 0–24 h period after surgery were significantly lower in group P (all P < 0.05). The scores of QoR-15 scale were higher in group P at 24 h postoperatively than those in group C (P < 0.05). Patients in group P showed lower plasma levels of HMGB1 than group C at 1 day after surgery (P < 0.05), and the rate of complications didn’t differ between both groups. Conclusions Older people undergoing HA receiving a PENG block for perioperative analgesia experience improved early postoperative cognitive function, reduced postoperative pain, higher quality of recovery, and less postoperative inflammatory response. Trial registration Chictr.org.cn identifier ChiCTR2200061055 (Date of registry: 15/06/2022, prospectively registered).